Incorporation of a gravity wave momentum deposition parameterization into the Venus Thermosphere General Circulation Model (VTGCM). Issue 1 (31st January 2013) - Zalucha, A. M.; Brecht, A. S.; Rafkin, S.; Bougher, S. W.; Alexander, M. J.
Abstract : The gravity wave‐drag parameterization of Alexander and Dunkerton (1999) was implemented into a Venus Thermosphere General Circulation Model (VTGCM) to investigate breaking gravity waves as a source of momentum deposition in Venus' thermosphere. Previously, deceleration of zonal jets on the morning and evening terminators in models was accomplished via Rayleigh friction, a linear drag law that is not directly linked to any physical mechanism. The Alexander and Dunkerton (1999) parameterization deposits all of the momentum of a breaking wave at the breaking altitude and features a spectrum of wave phase speeds whose amplitudes are distributed as a Gaussian about a center phase speed. We did not find a combination of wave parameters (namely, center phase speed, amplitude at center phase speed, and distribution width) to produce sufficient drag in the jet cores that would bring VTGCM density and nightglow emissions into agreement with Venus Express observations. The zonal wind shear from 100 to 120 km altitude is very strong. Gravity waves launched below 100 km either break in the strong shear zones below 115 km or are reflected and do not propagate into the jet core regions where drag is needed. The results we present demonstrate that parameterizations developed for the middle atmosphere do not work in the thermosphere and that appropriate damping mechanisms other than nonlinear breaking/saturation dominate and should be accounted for at these heights. Key Points: Gravity waves are investigated as a momentum source in Venus' thermosphere We did not find a set of gravity wave parameters consistent with observations Total internal reflection prohibits gravity waves from penetrating jet cores